Click chemistry derived sugar-based surfactants with various shapes: Synthesis and physical studies / Tammar Hussein Ali - Tammar, Hussein Ali (2015)
Surfactants are important bulk chemicals with diverse applications in various fields, ranging from food over detergents to industrial products like lubricants. Growing environmental awareness and limitation of petrochemical resources have shifted the focus towards the utilization of renewable resources. Good candidates are sugar based surfactants. A series of new surfactants were prepared by click chemistry using functionalized glucosides as the hydrophilic domain. Variations of the molecular structure led to three different shapes, i.e. Y-shape, X-shape and reverse Y-shape, referring to the geometric arrangements of the hydrophobic and hydrophilic domains, respectively. Since the shape of a surfactant affects its molecular assembly behaviour, each surfactant type gives rise for specific applications. Despite the application of multi-step syntheses, reasonable overall conversions yields, ranging from 20 to 55%, were obtained. The surfactants were characterized by NMR spectroscopy (1H as well as 13C) and mass spectrometry, and their physical behaviour was investigated by optical polarizing microscopy and systematic surface tension measurements of aqueous solutions to determine the CMC. Except for one hydrophobic dominant reverse-Y-shape compound all surfactants exhibited very low Krafft temperatures, indicating good molecular solubility in water. The surface dominance of the hydrophilic domain, especially for X and Y-shape surfactants, led to preferred spherical aggregation in water, suggesting good emulsifying properties for oil in water. In fact, some of the surfactants led to metastable O/W-emulsions in absence of a polymeric stabilizer and required several days to separate. The surfactants may find technical applications particularly for water based emulsion systems, like e.g. oil recovery or pharmaceutics.